MODIFIKASI SISTEM MONITORING KEAMANAN LOCAL AREA NETWORK BERBASIS NOTIFIKASI TELEGRAM DENGAN SNORT DAN HONEYPOT DI POLITEKNIK PENERBANGAN SURABAYA - Nyaris Pambudiyatno; Bambang Bagus Hariyanto; Yuyun Suprapto; Ade Irfansyah (Jurnal Penelitian, 2025)
This research aims to develop a network security system based on the Network Intrusion Detection and Prevention System (NIDPS) that combines Snort and Honeypot, and is integrated with Telegram to provide instant notifications related to network anomalous activity. The research method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Snort plays a role in detecting cyber threats through network traffic analysis, while Honeypot serves to trick attackers by mimicking the original server. The fail2ban feature was added to block repeated attack attempts such as brute force. Quality of Service (QoS) testing, which includes throughput, packet loss, delay, and jitter, shows that the system is able to detect a wide range of threats without significantly impacting network performance. The system developed is not only effective in detecting cyberattacks, but also provides real-time alerts through Telegram, thus helping in mitigating potential damage. Further developments are proposed to improve detection against more complex attacks and optimize the system's integration with Telegram for faster notifications.